Advanced Glycation End-Products and Hyperglycemia Increase Angiopoietin-2 Production by Impairing Angiopoietin-1-Tie-2 System - Alessandra Puddu; Roberta Sanguineti; Davide Maggi; Massimo Nicolò; Carlo E. Traverso; Renzo Cordera; Giorgio L. Viviani (Journal of Diabetes Research)
The angiopoietin-Tie-2 system plays a crucial role in the maintenance of endothelial integrity. Hyperglycemia and advanced glycation end-products (AGEs) are involved in endothelial cell dysfunction responsible of the pathogenesis of microvascular complications of diabetes. Here, we investigated whether glycated serum (GS) or hyperglycemia (HG) affect the angiopoietin-Tie-2 system in the microvascular endothelial cells HMEC-1. We found that culture for 5 days in the presence of AGEs and HG (alone or in combination) decreased cell proliferation, increased reactive oxygen species (ROS) production, and reduced ratio between the oxidized and the reduced form of glutathione. Since angiopoietin-1 (Ang-1) signaling regulates angiopoietin-2 (Ang-2) expression through inactivation of the forkhead transcription factor FoxO1, we investigated intracellular signaling of Ang-1 and expression of Ang-2. HG and AGEs reduced phosphorylation of Akt and abrogated phosphorylation of FoxO1 induced by Ang-1 without affecting neither Tie-2 expression nor its activation. Furthermore, AGEs and/or HG induced nuclear translocation of FoxO1 and increased Ang-2 production. In conclusion, we demonstrated that both hyperglycemia and AGEs affect the angiopoietin-Tie-2 system by impairing Ang-1/Tie-2 signaling and by increasing Ang-2 expression. These results suggest that therapeutic strategies useful in preventing or delaying the onset of diabetic vascular complications should be aimed to preserve Ang-1 signaling.